Riometer Records of 30 MHz Cosmic Noise at Syowa Station, Antarctica in 1972 - イソザキ, ススム; ミヤザキ, シゲル; ISOZAKI, Susumu; MIYAZAKI, Shigeru (National Institute of Polar Research, 1973)
P(論文) departmental bulletin paper